Algorithms for synthesis of functionally stable wireless sensor network - Barabash, Oleg; Sobchuk, Valentyn; Sobchuk, Andrii; Musienko, Andrii; Laptiev, Oleksandr (Національний технічний університет "Харківський політехнічний інститут", 2025)
Therefore, the work is devoted to solving the current scientific problem of developing an algorithm for searching for the optimal structure of a wireless sensor network. An algorithm for finding a lower bound for the number of removed vertices and an algorithm for finding a lower bound for the number of removed vertices taking into account redundant communication lines have been developed. It has been established that first of all it is necessary to determine the complete set of minimal graph sections and their power. An algorithm for finding the optimal structure of a wireless sensor network has been developed, which consists of nine steps and can be used to synthesize the structure of wireless sensor networks that have the ability to self-organize in order to find its optimal structure. It is shown that the proposed algorithm has a high level of convergence and provides the desired result for a finite number of iterations, which is much better than finite search.

Робота присвячена вирішенню актуального наукового завдання розробки алгоритму пошуку оптимальної структури бездротової сенсорної мережі. Розроблено алгоритм знаходження нижньої оцінки числа видалених вершин та алгоритм знаходження нижньої оцінки числа видалених вершин з урахуванням надлишкових ліній зв'язку. Встановлено, що насамперед необхідно визначити повну сукупність мінімальних перерізів графа і їх потужності. Розроблено алгоритм пошуку оптимальної структури бездротової сенсорної мережі, який складається з дев'яти кроків та може бути застосований для синтезу структури бездротових сенсорних мереж, які мають здатність до самоорганізації, з метою пошуку її оптимальної структури. Показано, що запропонований алгоритм має високий рівень збіжності та за скінченне число ітерацій забезпечує потрібний результат, що значно краще скінченного перебору.
Алгоритми синтезу функціонально стійкої бездротової сенсорної мережі
Keywords: wireless network; sensor networks; functional stability; algorithms; structure synthesis; convergence; бездротові мережі; сенсорні мережі; функціональна стійкість; синтез структури; збіжність; алгоритми синтезу